Perfect electromagnetic and sound absorption via subwavelength holes array - Wang Yanqin (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
Broadband sound absorption at low frequency is notoriously difficult because the thickness of the absorber should be proportional to the working wavelength. Here we report an acoustic metasurface absorber following the recent theory developed for electromagnetics. We first show that there is an intrinsic analogy between the impedance description of sound and electromagnetic metasurfaces. Subsequently, we demonstrated that the classic Salisbury and Jaumann absorbers can be realized for acoustic applications with the aid of micro-perforated plates. Finally, the concept of coherent perfect absorption is introduced to achieve ultrathin and ultra-broadband sound absorbers. We anticipate that the approach proposed here can provide helpful guidance for the design of future acoustic and electromagnetic devices.